Studio & location lighting secrets for digital photographers - Sammon, Rick (Wiley, 2009)
"Written by Canon Explorer of Light Rick Sammon and leading fashion and studio photographer Vered Koshlano, this guide is packed with professional advice on the essential element of photography: lighting. It provides detailed information and insider secrets that are bound to make you a better photographer. You'll learn the basics of studio lighting as well as how to achieve special effects"--Resource description page